Transcortical sensory aphasia heralding SARS-Cov-2-induced autoimmune encephalitis with gyral restricted diffusion hyperintensities: a novel case report - Chakraborty, Arka Prava; Pandit, Alak; Dutta, Ajitava; Das, Shambaditya; Ganguly, Goutam; Dubey, Souvik (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery, 2022)
Background Coronavirus disease 2019 (CoVID-19), primarily thought of as a respiratory system disease is actually a multi-system disease with immunological implications. CNS involvement in COVID has been explained in recent literature mainly for stroke, encephalopathy, encephalitis, acute disseminated encephalomyelitis and myelopathy. There are few studies characterizing clinical spectrum of COVID autoimmune encephalitis. We present a unique case of post-COVID autoimmune encephalitis in a diabetic male presenting with language dysfunction and novel radiologic findings. Case presentation Patient admitted to inpatient department of a tertiary care hospital of India was evaluated by bedside clinical examination, routine blood tests, CSF study with intrathecal SARS-Cov-2 antibody detection, commercially available tests for autoimmune encephalitis, neuroviral panel with HSV PCR, EEG, 3-Tesla MRI and PET scan. Patient was found to have personality change and transcortical sensory aphasia in the outset of COVID encephalitis. MRI findings like temporal involvement and insular ribboning are also being reported. The patient was treated with IV immunoglobulin and is on an improving course. Conclusions This case reports dysphasia due to COVID-mediated injury to the language networks, with novel radiologic findings. Role of parainfectious versus immune etiology is also discussed. Further studies are needed to elucidate the mechanism and clinical spectrum of post-COVID autoimmune encephalitis.